Work in progress - An educational tool for teaching linear and control systems - Gonzalez, Emmanuel A. (Animo Repository, 2007)
Control systems engineering has been part of every engineering field. Whether in electrical, electronic, computer, mechanical, or chemical engineering, control systems play a relevant part both in the academe and in the industry. Thus, there is a big need to develop strategies which will help undergraduate and graduate students of engineering learn more and obtain hands-on training when it comes to linear systems theory and control systems engineering. Furthermore, learning must be both conceptual and practical. In this paper, we present an educational tool, which is currently being developed by the authors, that can be used in teaching linear systems theory and control systems engineering in the undergraduate and graduate levels. The educational tool is a hardware-software package designed to be used by instructors and students as well. Moreover, the educational tool comes with a manual for guided instructions. This paper discusses the complete conceptual design of the project and the proposed learning and implementing strategies. An evaluation plan will be used in determining the effectiveness of the tool upon its integration in an Electronics and Communications Engineering (ECE) and Computer Engineering (CoE) curricula. © 2007 IEEE.